Evolution of hardness and modulus within a cold-rolled in situ dendrite-reinforced metallic glass matrix composites. (May 2015) - Sun, X. H.; Yang, H. J.; Wang, Y. S.; Pan, S. P.; Wang, Z. H.; Xu, B. S.; Qiao, J. W.
Abstract : Cold-rolled in situ dendrite/metallic glass matrix (MGM) composites with a composition of Ti48 Zr18 V12 Cu5 Be17 exhibit a fact that modulus and hardness of matrix is decreased with the increasing in thickness reduction, while the modulus of dendrites remains constant, and hardness tends to increase sharply with the increase in thickness reduction < 30% and then it approximately remains constant. Free volumes created by plastic deformation lead to the decrease of the matrix modulus. Dendrites are restricted by surrounding matrix, which results in the modulus of dendrites constant. Multiplication of shear bands is the dominant mechanism affecting the hardness of the matrix. The present study gives a guideline to predict the evolution of hardness and modulus in both dendrites and glass matrix in such dual-phase composites.